Developing Materials of Writing Course Using Graphic Organizers for the English Department Students - Elhawwa, Tazkiyatunnafs (Journal on English as a Foreign Language (JEFL), 2015)
The study is intended to develop Writing III Course materials using graphic organizers for the fourth-semester students of English Education Study Program of IAIN Palangka Raya. The Research and Development (R & D) design was employed in this study. It included the stages: Â need analysis, description of the purpose, selection and development of material type, production of proto-material, production of pedagogical material, expert validation, field testing (trying-out), evaluation and revision (evaluation from try-out and the expert, and final product. The final product of this study was the instructional materials (six units for nine meetings) covering introduction to the essay (unit 1 for meetings 1-4), the illustration essay (unit 2 for meeting 5), the classification essay (unit 3 for meeting 6), the process essay (unit 4 for meeting 7), the comparison contrast essay (unit 5 for meeting 8), and the cause and effect (unit 6 for meeting 9). Each unit consisted of learning objective, topic, sub-topic, description, relevancy, and keywords. The materials serve for appropriate topics, clear models, stimulating learning, relevant activities, clear example, graphic organizers, and providing strategies.